Assortative Mating and Household Income Inequality in Argentina - Funes Leal, Víctor Exequiel (2015)
We use the decomposition method of (Greenwood et al., 2014) to assess the contribution of Assortative Mating to household income inequality for Argentina. We estimate the Gini coefficient and contingency tables for for spouses’ educational attainment in order to simulate the outcomes of random mating. We find that Assortative Mating plays a minor role in the determination of household income inequality, despite explaining about 10% of inequality, the results have very little robustness to changes in parameters and are also at odds with values of a number of sorting indicators.